Call for a consensual definition of dyslipidemia in coronary angiography trials - Clerc, Aurélien; Togni, Mario; Cook, Stephane (Frontiers in Cardiovascular Medicine, 2025)
Dyslipidemia is extensively analyzed in clinical trials investigating its role as a risk factor for coronary artery disease (CAD). However, its definition varies vastly among studies, leading to different attributions to the variable dyslipidemia. The objectives of this study are to verify the hypothesis of a lack of a consensual definition of dyslipidemia in coronary angiography studies and to propose a consensual definition of dyslipidemia, considering the influence of each serum lipid parameter on mortality. A systematic search of coronary angiography studies focusing on dyslipidemia was conducted. We listed definitions and their references in the 258 articles the research found. Out of the 258 articles retrieved in the search, 52 studies (20%) provided a definition of dyslipidemia, and 20 (8%) mentioned the source. We identified 39 different definitions. To mitigate misinterpretations of cardiovascular risk factors, we propose the use of the “lipid triad” components to define dyslipidemia: LDL-cholesterol >3.0 mmol/L for primary prevention and >2.6 mmol/L or >1.4 mmol/L for secondary prevention in patients over/under 75 years old, respectively; or HDL-cholesterol <1.3 mmol/L (women) and <1.0 mmol/L (men); or triglycerides >1.7 mmol/L.